Thermodynamics of Micellization of Nonionic Surfactant Tween-40 in Presence of Additive Chloramine-T Using Clouding Phenomenon - A. A. Patil; T. J. Patil (E-Journal of Chemistry)
The phenomenon of solubilization of nonionic surfactant Tween-40 has been studied through the influence of additive chloramine-T in aqueous medium by measuring the cloud points (CP) of the pure surfactant and with chloramine-T. The CP of pure surfactant was found to be increased with increasing concentration of Tween-40. The CP of mixed system shows increasing trends with increased chloramine-T. This is mainly due to increased micelle concentrations. The influence of chloramine-T on the cloud point of Tween-40 is a clear indication that the phenomenon of clouding is associated with the different micelles coalescing. Considering cloud point as threshold temperature of the solubility, the thermodynamic parameters of clouding process (ΔG0cl, ΔH0cl and ΔS0cl) have been evaluated using “Phase Separation Model”. The phase separation results from micelle-micelle interaction. It was found that the overall clouding process was exothermic and ΔH0cl > TΔS0cl indicating that the process of clouding was guided by both enthalpy and entropy. This work supports the conjecture that the clouding is critical phenomenon rather than the growth of micelles. Findings of the present work supports to made the probable evidence of electrolyte-surfactant interactions in aqueous medium.